Effect of γ-irradiation on Microbiological, Biochemical and Sensory Qualities of Commercial Powdered Cocoa Beverage Premix - Pradeep Puligundla (Science Faculty of Chiang Mai University, 2019)
Low-dose gamma irradiation has been considered effective for improving the microbiological safety of fresh and processed foods. In the present study, γ-rays in the dose-range of 0-15 kGy were used for microbial decontamination of commercially available, ready-to-use powdered cocoa beverage premix. Premix was artificially inoculated with Aspergillus oryzae, Saccharomyces cerevisiae and Bacillus cereus. A complete inactivation of the tested microbes was observed with 10-15 kGy in inoculated and with 2.5-5 kGy in non-inoculated, commercial cocoa beverage premixes. Thiobarbituric acid (TBA) values increased linearly with the magnitude of dose. The peroxide value, amino nitrogen content and protein solubility were not significantly affected by the γ-irradiation. The overall sensory quality of irradiated premix was not significantly affected with the radiation doses less than 10 kGy. The results indicated that low-dose γ-radiation (up to 10 kGy) can be used to improve the microbiological quality of powdered cocoa beverage premixes before being loaded into vending machines.